2016
DOI: 10.1016/j.neo.2016.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Changes, Cadherin Switching, and Growth Suppression in Pancreatic Cancer by GALNT6 Knockdown

Abstract: Pancreatic cancer reveals the worst prognosis among human cancers with little improvement in its clinical outcome in the last three decades. We previously suggested that polypeptide N-acetylgalactosaminyltransferase 6 (GALNT6), which catalyzes O-type glycosylation of Mucin 1, might be a promising molecular target for drug development for breast cancer. In this study, we report upregulation of GALNT6 in pancreatic cancer cells where Mucin proteins are highly O-glycosylated. We found that knockdown of GALNT6 wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 22 publications
1
48
0
Order By: Relevance
“…Knockdown of GalNAc-T6 was recently shown to induce a switch from P-cadherin to E-cadherin expression in pancreatic cancer cells (67). However, our colon transcriptome data indicated rather an opposite shift from E-cadherin to P-cadherin expression (Fig.…”
Section: Cancer-associated Expression Of Human Pp-galnac-t6mentioning
confidence: 54%
See 2 more Smart Citations
“…Knockdown of GalNAc-T6 was recently shown to induce a switch from P-cadherin to E-cadherin expression in pancreatic cancer cells (67). However, our colon transcriptome data indicated rather an opposite shift from E-cadherin to P-cadherin expression (Fig.…”
Section: Cancer-associated Expression Of Human Pp-galnac-t6mentioning
confidence: 54%
“…In breast cancer, overexpression of GalNAc-T6 was reported to decrease cellular adhesion and disrupt mammary acinar morphogenesis (66,67,82). Furthermore, it has been shown that GalNAc-T6 expression in pancreatic cancer causes a switch from E-cadherin expression to P-cadherin expression affecting cellular adhesion to the underlying matrix (67).…”
Section: Cancer-associated Expression Of Human Pp-galnac-t6mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown to be upregulated when cells are differentiating, and in malignancy [21][22][23][24]. Expression is minimal in normal tissues [21].…”
Section: Molecular Geneticsmentioning
confidence: 99%
“…pp-GalNAc-T6 has also been studied once in pancreatic cancer [23,55]. pp-GalNAc-T6 expression is rare in normal ductal epithelium of the pancreas.…”
Section: Role In Cancermentioning
confidence: 99%